7z-3(4-z)=5(2z)+12

Simple and best practice solution for 7z-3(4-z)=5(2z)+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z-3(4-z)=5(2z)+12 equation:


Simplifying
7z + -3(4 + -1z) = 5(2z) + 12
7z + (4 * -3 + -1z * -3) = 5(2z) + 12
7z + (-12 + 3z) = 5(2z) + 12

Reorder the terms:
-12 + 7z + 3z = 5(2z) + 12

Combine like terms: 7z + 3z = 10z
-12 + 10z = 5(2z) + 12

Remove parenthesis around (2z)
-12 + 10z = 5 * 2z + 12

Multiply 5 * 2
-12 + 10z = 10z + 12

Reorder the terms:
-12 + 10z = 12 + 10z

Add '-10z' to each side of the equation.
-12 + 10z + -10z = 12 + 10z + -10z

Combine like terms: 10z + -10z = 0
-12 + 0 = 12 + 10z + -10z
-12 = 12 + 10z + -10z

Combine like terms: 10z + -10z = 0
-12 = 12 + 0
-12 = 12

Solving
-12 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6/7x6/7x6/7 | | (3x-5)+(2x+5)=180 | | 3x-5=-10-2x | | 5(2x-1)=-2(3x-5) | | -20=2x(-2-3) | | 3x+5=x-2(modx) | | 4(4d-3)=8d-36 | | (10a)/(5a^5*5) | | 3x-6=-x-6 | | 4=H | | 6(4-x)=5 | | y/6=-29 | | 7x-5x+x-3+4x= | | 10x-10+2=-20 | | X/3-9=8 | | 9z(3m+5r)= | | 23=2y-17 | | X-7+2x=43 | | 174+(84*x)=1350 | | -(z-8)= | | 6.4x-4+x-1.9= | | -16x+5x=4(3x+7) | | 8+4=20 | | 7(x+33)+9=5(x-2)-3x | | 2t^2-2t+6=0 | | 22n-36=0 | | X^2-1.4x+0.49=0.35 | | 2m+13=16 | | 3(x-2)+5(x-2)=15x | | 3(5x+2)=2(3-6) | | m+17=34 | | 10x-10+2=-26 |

Equations solver categories